OS DISCURSOS SOBRE EDUCAÇÃO DO CAMPO: UM ESTUDO DO CASO DA ESCOLA MUNICIPAL DE ENSINO FUNDAMENTAL VANDA MARIA DA SILVA - Murini, João Buzatti (2020)
Countryside education seeks to qualify and guarantee access to education for the Countryside populations, through educational policies and programs. It came up with the peasants' league, characterized by the demand of the education movement of the field popular classes, with a social and political focus, of the organization of the popular classes. The aim of this study is to analyze speeches that allude to field education present in the Political Pedagogical Project of the Municipal Elementary School Vanda Maria da Silva in the municipality of Jaguari. The research was characterized as: qualitative, exploratory, descriptive, explanatory and documentary. The analyzed documents were federal and state regulatory marks, Pedagogical Political Project (PPP), linguistically-discursively in relation to the concepts of the field education, and the data analysis used the theoretical-methodological approach of Critical Discourse Analysis (ACD). It is concluded that the indices found on education in the countryside appear in the PPP, aligned in a generic way in relation to education in the countryside, we also analyze that education in the countryside has many particularities, being necessary to respect the specific social and cultural diversity of the population of the countryside.